Situation Report: Hungary, 29 December 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Janos Peter Again on the Necessity of Danubian Cooperation License Contract between the Budapest Ganz Works and English Electric Company Troubles with Laid-off Hungarian Coal Miners Contacts with East European Countries and Other Parties